Electronic government design, applications, and management - Grönlund, Åke. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2002)
While not specifically defined, electronic government has become a common term to describe all of the processes, administrative and democratic, that combine to constitute public sector operations. Electronic Government: Design, Applications and Management examines the changes faced by the public sector, as the use of IT significantly increases. This book, geared toward practitioners, professionals, decision makers and students strives to examine the challenges and opportunities involved in the implementation and use of IT into organizations.